CRITICAL PSYCHOLOGY FOR SOUTH AFRICAN TRANSFORMATION? - Palmary, Ingrid (PINS-Psychology in Society, 2025)
Fox, D, Prilleltensky, I & Austin, S (eds) (2009) Critical psychology: An introduction (Second edition). London: Sage. ISBN 978-1-84787-173-2. Pages 470. The launch of the Apartheid Archive Project fifteen years after the end of apartheid in South Africa is a fitting time to reconsider the role of psychology in the social and political history of the country. The book Critical psychology: An introduction provides an opportunity to revisit key critiques of the discipline of psychology, whilst perhaps more importantly for a South African audience, to consider their relevance across geographical and political contexts. The book draws together the ideas of a wide group of writers, many of whom have been central to the development of critical psychology internationally. As such, they reflect on debates and ideas that, over the past fifteen years, have shaped how psychologists have critiqued their discipline and, for South African psychologists, tackled post-apartheid social issues. There is no doubt that psychology was used in the service of apartheid ideology. However there have equally been pockets of resistance by psychologists who have attempted to critique, rethink and at times, abandon the discipline. This book provides the impetus to reflect on and reconsider the importance of these debates in the South African context. The editors of this book emphasize that they aim to create a community of critical psychologists and the breadth of the contributions already points to the success of this project. Written at a time when critical psychology is becoming a more commonly accepted topic in South Africa and a more easily adopted position for psychologists generally, this book summarizes some of the key debates that have resulted in the creation of critical psychology and the challenges a critical perspective poses to the existing assumptions underpinning the discipline. I will give a brief overview of the book before focusing on three main themes emphasized in the book that I think are of relevance for a South African audience, namely, the nature of the subject of psychology, the possibilities of psychological practice being a force for liberation, and what a more critically engaged alternative psychology might look like.